KOALISI TRANSAKSIONAL PARTAI POLITIK DALAM PEMILIHAN UMUM KEPALA DAERAH DI LAMPUNG - Hertanto Hertanto; Nidzammuddin Ahmad Sulaiman (Program Studi PPKn FIS UNJ & Asosiasi Profesi PPKn Indonesia, 2013)
This paper aims to explain why most political parties, particularly the Prosperous Justice Party (PKS), the coalition tend to behave pragmatically, ie, do not form a stable coalition party/firm to win mass support. The findings of the study explained that the attitude and behavior of this coalition further highlight the principle of pragmatism transactional, ie the act of looking for a great opportunity to win a pair of candidates who are influenced by the politics of money and also for the purpose of raising funds for the party's survival and existence it self.